Transport Phenomena in Liquid Composite Molding Processes - Delgado, João M.P.Q.; Barbosa de Lima, Antonio Gilson; do Nascimento Santos, Mariana Julie; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides valuable information on polymer composite manufacturing, with a focus on liquid molding processes and the resin transfer molding technique (RTM). It presents and discusses emerging topics related to the foundations, engineering applications, advanced modeling and experiments regarding the RTM process. A valuable resource for engineers, professionals in industry and academics involved in this advanced interdisciplinary field, it also serves as a comprehensive reference book for undergraduate and postgraduate courses.
Introduction -- The liquid composite molding process -- Advanced experiments in RTM processes -- RTM process modeling.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Polymers; Manufactures; Engineering Thermodynamics, Heat and Mass Transfer; Polymers; Machines, Tools, Processes